Determinative ratios of a rheological model of a discrete medium with a variable angle of internal friction - Dorofeyev, O.A.; Kovtun, V.V. (Problems of Tribology, 2020)
The article deals with determining ratios of a rheological model of a discrete medium with a variable angle of internal friction, which reflect the characteristic features of deformation of a discrete material: the influence of internal Coulomb friction and the manifestation of dilatancy at all stages from the beginning of loading to the onset of the limit state. The relations are formulated in the form adopted in the theory of plastic flow of material with a variable flow surface. This allowed us to use a well-tested apparatus of the theory of rigidity of a solid body to describe the process of deformation of a discrete material. To formulate the relations, new concepts of stresses and strains occurring on special conjugate planes, which are convenient for describing the deformation of a discrete material, have been introduced. The values of its variable parameters necessary for the use of the model in the engineering calculations are proposed to determine by the results of special laboratory tests of macro-samples of a specific material for biaxial compression in conditions of flat deformation.